Enteral tranexamic acid attenuates vasopressor resistance and changes in α1-adrenergic receptor expression in hemorrhagic shock. Issue 2 (August 2017) - Santamaria, Marco Henry; Aletti, Federico; Li, Joyce B.; Tan, Aaron; Chang, Monica; Leon, Jessica; Schmid-Schönbein, Geert W.; Kistler, Erik B.
Abstract : BACKGROUND: Irreversible hemorrhagic shock is characterized by hyporesponsiveness to vasopressor and fluid therapy. Little is known, however, about the mechanisms that contribute to this phenomenon. Previous studies have shown that decreased intestinal perfusion in hemorrhagic shock leads to proteolytically mediated increases in gut permeability, with subsequent egress of vasoactive substances systemically. Maintenance of blood pressure is achieved in part by α1 receptor modulation, which may be affected by vasoactive factors; we thus hypothesized that decreases in hemodynamic stability and vasopressor response in shock can be prevented by enteral protease inhibition. METHODS: Rats were exposed to experimental hemorrhagic shock (35 mm Hg mean arterial blood pressure for 2 hours, followed by reperfusion for 2 hours) and challenged with phenylephrine (2 μg/kg) at discrete intervals to measure vasopressor responsiveness. A second group of animals received enteral injections with the protease inhibitor tranexamic acid (TXA) (127 mM) along the small intestine and cecum 1 hour after induction of hemorrhagic shock. RESULTS: Blood pressure response (duration and amplitude) to phenylephrine after reperfusion was significantly attenuated in animals subjected to hemorrhagic shock compared with baseline and control nonshocked animals and was restored to near baseline by enteral TXA. Arteries from shocked animals also displayed decreased α1 receptor density with restoration to baseline after enteral TXA treatment. In vitro, rat shock plasma decreased α1 receptor density in smooth muscle cells, which was also abrogated by enteral TXA treatment. CONCLUSION: Results from this study demonstrate that experimental hemorrhagic shock leads to decreased response to the α1 -selective agonist phenylephrine and decreased α1 receptor density via circulating shock factors. These changes are mitigated by enteral TXA with correspondingly improved hemodynamics. Proteolytic inhibition in the lumen of the small intestine improves hemodynamics in hemorrhagic shock, possibly by restoring α1 adrenergic functionality necessary to maintain systemic blood pressure and perfusion.